2009
DOI: 10.1080/03630260802626053
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of α-Thalassemia in the Dohuk Region of Iraq

Abstract: The molecular basis of alpha-thalassemia (alpha-thal) has been addressed by several studies from the eastern Mediterranean region, but not from Iraq. To address this issue, we studied 51 individuals with unexplained hypochromia and/or microcytosis, as well as nine patients with documented Hb H disease from the Dohuk region in northern Iraq. We used multiplex gap-polymerase chain reaction (gap-PCR), reverse hybridization, and sequencing for this purpose. It was found that the most common genotypes in those with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 19 publications
7
20
0
Order By: Relevance
“…Gene deletions including -a 17.4 , -a 26.5 , -a 20.5 , a2 -5nt , -a 3.7 , and -a 4.2 , mutations including a2 -Poly A1 , a2 -Poly A2 and a1 cd 59 G [ A point mutation and aaa anti-3.7 gene triplication have been reported in several studies from our country and the frequency of -a 3.7 deletion has been reported to be rather high as in other populations of Mediterranean basin [4,5]. The most common genotypes in Iraq were -a 3.7 /aa, -MED /aa and -a 3.7 /-a 3.7 which were detected in 65.1 % of the study group [6]. In the present study, 12 different alleles and 29 genotypes were identified.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Gene deletions including -a 17.4 , -a 26.5 , -a 20.5 , a2 -5nt , -a 3.7 , and -a 4.2 , mutations including a2 -Poly A1 , a2 -Poly A2 and a1 cd 59 G [ A point mutation and aaa anti-3.7 gene triplication have been reported in several studies from our country and the frequency of -a 3.7 deletion has been reported to be rather high as in other populations of Mediterranean basin [4,5]. The most common genotypes in Iraq were -a 3.7 /aa, -MED /aa and -a 3.7 /-a 3.7 which were detected in 65.1 % of the study group [6]. In the present study, 12 different alleles and 29 genotypes were identified.…”
Section: Discussionsupporting
confidence: 52%
“…Alpha-thalassemia is an autosomal recessive disorder characterized by microcytic hypochromic anemia and a clinical phenotype varying from almost-asymptomatic to lethal hemolytic anemia [6]. Alpha-thalassemia is often initially suspected on the basis of a routine full blood count.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular testing of 104 (50 male, 54 female) registered beta-thalassemia patients from Dohuk detected 12 mutations. The eight most common mutations observed accounted for 81.7% of the thalassemia alleles [51]. The mutations in descending order of frequency were: c.315+1G>A, c.135delC, c.17_18delCT, c.92+1G>A, c.92+6T>C, c.118C>T, c.27_28insG, and c.92+5G>C ( Table 2).…”
Section: Prevalence Of Beta-thalassemia Throughout the Middle Eastmentioning
confidence: 99%
“…In Iraq, beta-thalassemia is an evident health problem, specifically in the Dohuk region located in the northern part of the country [51]. The Dohuk region lies midway between Iran, Turkey and Syria, countries also characterized by a relatively high frequency of beta-thalassemia.…”
Section: Prevalence Of Beta-thalassemia Throughout the Middle Eastmentioning
confidence: 99%
See 1 more Smart Citation